Effect of Partial Excision of Early Taproots on Growth and Components of Hydroponic Carrots - Masaru Sakamoto; Masanori Wada; Takahiro Suzuki (Horticulturae, 2020)
Hydroponics provides a stable root environment that can be easily controlled. In this paper, we investigated the effect of partial excision of early taproots of hydroponic carrots on their growth and components. Carrot taproots were excised after 30 days from sowing at 5 cm, 10 cm, and 15 cm from the stem base (C5, C10, and C15) and compared with nonexcised control plants. Time-course measurements revealed the taproot lengths of C10 and C15 plants gradually decreased. After 28 days of treatment, C5 taproot tips showed the most rounded shape among root-excised plants. Control plants possessed long taproots that were not enlarged at the site more than 15 cm from the stem base. Taproot fresh weight was lower in C5 plants and higher in C15 plants compared with controls. Although taproot sugar concentrations did not differ between treatments, total phenol concentration was higher in C5 taproots. These data suggest that partial removal of early taproots can regulate the shape and ingredients of hydroponic carrots.